1993
DOI: 10.1148/radiology.187.3.7684528
|View full text |Cite
|
Sign up to set email alerts
|

Malignant esophageal strictures: treatment with a self-expanding nitinol stent.

Abstract: A self-expanding esophageal nitinol stent was implanted under fluoroscopic guidance in 40 patients with malignant esophageal strictures and clinically significant dysphagia. The strictures were caused by squamous cell carcinoma (n = 14), adenocarcinoma (n = 12), recurrent anastomotic carcinoma (n = 8), and mediastinal tumors (n = 6). Eight stents were balloon dilated to maximum diameter immediately after insertion. Sixteen stents self-expanded to maximum diameter within 24 hours, and the other stents expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(67 citation statements)
references
References 0 publications
7
58
1
1
Order By: Relevance
“…Procedure-related mortality was low (3%) and significant morbidity also low (one transient melena and one partial stent migration -6%). This compares well with the series of Cwikiel et al 7 in which one patient of 40 died three days after stenting, and the series of Raijman et al 8 in which two patients of 14 died one and six days respectively after the procedure, one from aspiration pneumonia and the other from myocardial infarction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Procedure-related mortality was low (3%) and significant morbidity also low (one transient melena and one partial stent migration -6%). This compares well with the series of Cwikiel et al 7 in which one patient of 40 died three days after stenting, and the series of Raijman et al 8 in which two patients of 14 died one and six days respectively after the procedure, one from aspiration pneumonia and the other from myocardial infarction.…”
Section: Discussionsupporting
confidence: 88%
“…In 1990, Domschke et al reported the first small series of self-expanding metal mesh stents 6 and in 1993, Wojciech Cwikiel et al published a large series of successful implantations of self-expanding nitinol mesh stents in 40 patients. 7 This paper describes our initial experience with the nitinol stent.…”
mentioning
confidence: 99%
“…[4, [26][27][28][29]. One patient had a single hematemesis withoutfurther problems [28], one stent migrated [29], and two were placed incorrectly [30].…”
Section: Twentymentioning
confidence: 99%
“…Dyspha gi a was gra ded on a sca le of 0 to 4 ac cording to Cwi ki el et al 5 Pa ti ents we re gra ded twi ce prior to the stent de li very and af ter the pro ce du re:…”
Section: Pa Ti Entsmentioning
confidence: 99%